Adaptasi Alat Ukur Keterlibatan Pembelajar Daring Pada Mahasiswa Di Indonesia - Sakina Rahmania; Lucia Retno Mursitolaksmi Royanto (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2021)
Online learning is a ‘new normal’ learning method since the policy of school from home has been established by the government due to Covid-19 pandemic. Student engagement in online learning environment needs to be evaluated to measure the effectiveness of teaching and learning activities. So far, there has not been any measuring tool for online student engagement in Indonesia. There is a measuring tool called Online Student Engagement (OSE) developed by Dixson (2010) and has been proved for its reliability and validity in measuring online student engagement among American Students. Hence, to be used in the context of online learning in Indonesia, this reaserch is aimed to adapt the OSE by following the guidelines and methods of cross-cultural adaptation of self-report measures by Beaton et al. (2000) which include (1) translation, (2) synthesis, (3) back translation, (4) expert committee review, (5) pretesting, (6) submission and appraisal of all written reports. This instrument consists of 19 items that represent the four dimensions of student engagement. Based on pretesting on 156 college students from various university in Indonesia, the reliability coefficient of this adapted instrument is 0,936. The confirmatory factor analysis (CFA) of this measurement shows its validity coefficient ranging from 0,453-0,949. The structural equation modeling also shows that the adapted instrument obtained a moderate model fit. Thus, the Online Student Engagement Scale adaptation are valid and reliable for use in future research to evaluate the level of student engagement in online learning environment.